Perkembangan Penyajian Tari Raddat Alon-Alon di Desa Matang Danau Kecamatan Paloh Kabupaten Sambas - Milda; Ismunandar; Mega Cantik Putri Aditya (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
This research purposed to describe the development of the presentation of the Raddat Alon-Alon Dance in Matang Danau Village. The method in this study is descriptive qualitative with an ethnochoreology approach. Data collection techniques used are observation, interview and documentation techniques. The results of this study indicate that the development of the presentation of the Raddat Alon-Alon Dance consists of several aspects, namely floor design, make-up, costume, and performance venue. The floor design which was initially horizontal has developed into a variety. Natural make-up has developed into a more complex one by emphasizing lines and sharpening facial expressions. The costume initially only used baju kurung and bannang ammas cloth and used a bun, then developed by adding the use of lotus, sash, and flower and earring accessories. The performance venue used to be in an open field in the form of an arena, then developed into a stage in the form of a proscenium. The results of the analysis show that the Raddat Alon-Alon Dance is still preserved so that it has developed in the dance. Keywords: Performance Development, Raddat Alon-Alon Dance, Matang Danau Village